Persepsi Masyarakat Terhadap Pelestarian Mangrove Di Desa Mengkapan Kecamatan Sungai Apit, Kabupaten Siak - Firda, Arlian; Rikizaputra; Afidah, Maratul (Universitas Lancang Kuning, 2025)
The Mangrove forests in Mengkapan Village are mangrove areas located in Siak Regency, mangrove forests have very important values and meanings, the issue of illegal logging is a concern for the surrounding community, therefore, this study aims to determine the perceptions and behavior of the community towards the ecological functions and preservation of mangrove forests, data collection techniques using purposive sampling, by determining the identity of respondents who match the research theme. In measuring the level of community participation in mangrove management, the highest result in the “never” answer category was 38.15%, indicating that respondents were not active in every phase of mangrove ecosystem management, from planning, implementation, utilization, to evaluation and supervision. On the Form of Community Participation, the highest average level was 54.23% for the answer category “never”. This indicates that respondents never participate in contributing ideas, labor, expertise, products, or funds for mangrove ecosystem management activities. Based on age, education level and occupation, 31% of the respondents were 18-29 years old; 30% were 30-41 years old; 26% were 42-45 years old; 9% were 54-65 years old; and 4% were above 65 years old. The younger age group (under 41 years old) participated less than the older age group (over 50 years old). 60% of respondents had completed senior high school (SMA), 19% had completed a diploma or bachelor's degree, 9% had completed junior high school, and 12% had completed elementary school. A person's understanding of new things is influenced by their level of education. The community generally follows the government education system. As many as 30% are government workers, 25% are traders, and 21% are freelancers, partners of forest rangers, tour guides and environmental activists. 8% of respondents worked in carpentry, including porters and electronic servicing; 5% were teachers, and 3% were fishermen. While 11% of the respondents are no longer working and 8% are retired.